Pengaruh Kualitas Kehidupan Kerja Dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Pada Kantor Camat Kecamatan Samalanga - Fakhriati, Fakhriati; Asnani, Asnani; Mursyidah, Mursyidah (JURNAL KEBANGSAAN, 2023)
This The study aims to analyze job satisfaction by reviewing factors of quality of work life and employee motivation. The study of 30 employees of Samalanga District Head, Bireuen Regency, with a quantitative approach and problem analysis using multiple linear regression. The results found (1) partially, quality of work life and motivation have a significant effect on employee job satisfaction with the value of the relationship model; Y = 4.120 + 0.426 X1 + 0.484 X2. Which means that a 10% increase in quality of work life also has an impact on increasing job satisfaction by 4.26%. Meanwhile, a 10% increase in work motivation from the usual will cause job satisfaction to increase by 4.84%. (2) Simultaneously, quality of work life and work motivation have a significant effect on job satisfaction by 66.8%.